Memory assistant in everyday living - Costa, Ângelo (2009)
Memory is one’s mental ability to store, to retain, and recall information, representing past and future, our dreams and/or expectations. However, as the human been ages, the capacity of remembering decreases as well the ability to pile up new memories, therefore affecting our quality-of-living and lowering our self- esteem. This configures a social and human dilemma. With the present work we intend to address some of these problems, in terms of a Personal Memory Assistant (PMA), in order to help the user to remember things and occurrences, making it in a proactive mode. It will also cater for some form of relaxation on the part of the user.